Perancangan dan Implementasi Sistem WIFI Berbasis Koin Untuk Usaha Warung Kopi Atau Kafe - Eriec Priyono; Azmuri Wahyu Azinar; Hindarto; Rohman Dijaya (LPPM UBHINUS MALANG, 2025)
The need for fast, stable, and affordable internet access is increasing along with the increasing dependence of society on information technology, especially in small business environments such as coffee shops and cafes. However, the operational costs of internet services are still a major challenge for micro-business owners. This study aims to design and implement a coin-based WiFi system that is independent, cost-effective, and easy to operate. This system integrates a coin sensor, microcontroller, and Raspberry Pi to detect coin denominations (Rp500 and Rp1000), automatically converts them into WiFi access duration, and records transactions in a local SQLite-based database. The web-based interface is built using Flask for ease of system administration and management. The research methods include literature studies, field observations, user interviews, and technical testing of sensor accuracy and network performance. Evaluations are carried out on download/upload speeds, latency, jitter, and packet loss to assess connection quality. The test results show that the system is able to detect coins with high accuracy and provide stable internet services according to the payment duration. The advantages of this system lie in its independence that does not depend on third-party applications, as well as its ability to be implemented in environments with technological and budget constraints. This system has the potential to be a viable alternative solution to expand internet access in the informal sector and drive digital transformation at the grassroots level.